(untitled) (Medico Legal Update, 2020)
A descriptive study at Al Hussein teaching Hospital in AL- Nasiriyah city to determine the knowledge of nurses’ in the emergency depatment. The most nurses working in this department after testing their information through the questionnaire prepared in calibrations did not have sufficient information about the pressure measurement. Nurses should enter courses on blood pressure measurement